PENGARUH KOMPETENSI AUDITOR, SISTEM PENGENDALIAN MUTU, KODE ETIK TERHADAP KUALITAS AUDIT DAN DAMPAKNYA PADA STAKEHOLDERS - Sarifudin, M; Asmara, Rina Yuliastuty (Buletin Studi Ekonomi, 2023)
This study aims to examine and analyze the effect of auditor competence, the effectiveness of the implementation of the Quality Control System, and the firmness of sanctions enforcement for violations of the Auditor Professional Code of Ethics on audit quality and its impact on stakeholders trust. This research was conducted on 480 active Public Accounting Firms in Indonesia by random sampling of 83 KAPs with partners and senior auditors representing KAPs. The data analysis method was carried out quantitatively by processing a list of questions that were processed in the form of numbers and the discussion was carried out through statistical calculations using SmartPLS 3.2.9. The test results show that the competence of auditors and the effectiveness of the application of QCS have no effect on audit quality. Meanwhile, the firmness of sanctions enforcement for violations of the auditor's professional code of ethics has an effect on audit quality and has an impact on stakeholders trust. This shows that the stricter the enforcement of sanctions for violations of the auditor's professional code of ethics, the higher the quality of the resulting audit. Good audit results provide confidence for stakeholders, especially investors, as a basis for investment considerations.